SO2SAFE - Enzymatic SO2 Biosensor for Rapid Food Safety Monitoring. (2017) - Jubete, E.; Jaureguibeitia, A.; Añorga, L.; Lamas-Ardisana, P.J.; Martínez, G.; Serafín, V.; Cabañero, G.; Ramos, E.; Salleres, S.; Grande, H.J.; Albizu, A.
Abstract: An amperometric sulfite biosensor was developed based on disposable screen printed electrodes (SPEs) and sulfite oxidase (SOx) enzyme. The developed biosensor shows good sensitivity (62 nA/ppm), reproducibility (RSD = 4%; n = 5) and a linear range of 15-1000 ppm. The applicability of the biosensor for the analysis of sodium metabisulfite in shrimp farm samples was demonstrated successfully.